A simple multiplex polymerase chain reaction assay for rapid identification of the common pathogenic dermatophytes:Trichophyton interdigitale, Trichophyton rubrum, and Epidermophyton floccosum - Sama Faramarzi; Marjan Motamedi; Ali Rezaei-Matehkolaei; Shima Aboutalebian; Saham Ansari; Mojtaba Didehdar; Mehran Bahadoran; Hossein Mirhendi (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: The most common etiological agents of human dermatophytosis in various parts of the world are Trichophyton rubrum, Trichophyton interdigitale, and Epidermophyton floccosum. The main aim of this study was to design and evaluate a simple and straightforward multiplex polymerase chain reaction (PCR)assay for reliable identification/differentiation of these species in clinical isolates.Materials and Methods: The reliable sequences of several molecular targets of dermatophytes species were used to design a multiplex PCR for the identification of common pathogenic dermatophytes. The isolates and clinical specimens examined in this study included seven standard strains of dermatophytes, 101 isolates of dermatophytes and non-dermatophyte molds/yeasts which had already been identified by sequencing or PCR-restriction fragment length polymorphism (RFLP), and 155 clinical samples from patients suspected of cutaneous mycoses.Results: Species-specific primer pairs for T. rubrum and T. interdigitale/T. mentagrophytes were designed based on the sequence data of the translation elongation factor 1-alpha gene, and the primers for E. floccosum targeted the specific sequence of the internal transcribed spacer region (ITS). The multiplex PCR successfully detected T.rubrum, T. interdigitale/T. mentagrophytes, and E. floccosum strains that were identified by sequencing or PCR-RFLP. However, the primer pairs selected for T. interdigitale/T. mentagrophytes cross-reacted with Trichophyton tonsurans. In testing the PCR system directly for clinical samples, the proportion of positive multiplex PCR was higher than positive culture (68.1% vs. 55.4%, respectively).Conclusion: The multiplex assay could detect three common agents out of several causal agents of dermatophytosis, namely T. rubrum, T. interdigitale, and E. floccosum.Therefore, by adding pan-dermatophyte primers it can be used as a comprehensive detection/identification test.